Pengaruh Penerapan Kegiatan Keagamaan Terhadap Peningkatan Nilai Spiritual Siswa di MAN 1 Watampone - Alfiah, Alfiah (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This paper is a research field, examines the application of the influence of religious activity to increased spiritual students in Watampone 1 MAN. The results showed that religious activity is any form of activity that has to do with religion, either belief or values that become routine in life and become a guideline through the relationship to the Allah swt. and the surrounding environment. For example prayer praying in congregation, pengajian, besarIslam day celebrations and other activities that are able to give more knowledge, to closer to Allah swt. The value contains the meaning of intelligence to put the person's life and behavior in the context of a broader meaning and rich, intelligence to rate that person's action or way of life more meaningful compared to the others. Religious activities that exist in MAN 1 Watampone consists of various activities, among others: to pray before studying, praying in congregation, dzuhur tadarus before it starts learning, praying Duha, guidance BTHQ, Islamic great day celebrations, lectures, spiritual race-race rote, Dawah, the pesantren ramadhan, Islamic studies. The application of proven and trusted religious values can increase the value of spiritual students.